Intestinal symptoms and Blastocystis load in schoolchildren of Paranaguá Bay, Paraná, Brazil - Seguí, Raimundo; Klisiowicz, Debora; Oishi, Camila Yumi; Toledo, Rafael; Esteban, José Guillermo; Muñoz-Antoli, Carla (Revista do Instituto de Medicina Tropical de São Paulo, 2017)
The symptomatology of Blastocystis cannot be attributed to any particular subtype, although can be related to a high Blastocystis infection load. One stool sample from each of 217 schoolchildren of Vale de Sol Paranaguá Bay (Paraná, Brazil) was collected. Three milliliters of each fixed stool sample were processed applying the formalin-ether concentration technique. After obtaining the overall prevalence of intestinal parasites, quantification was carried out in Blastocystis positive samples. A total of 75/217 (34.6%) children suffered from intestinal symptoms (abdominal pain and/or persistent diarrhea), of whom 41.3% (31/75) presented moderate/heavy Blastocystis load with a statistically significant risk to present intestinal symptoms (OR 0.039 [0.006-0.15]; p